Psychological correlates of suicidality in HIV/AIDS in semi-urban south-western Uganda - Rukundo, Godfrey Zari; Mishara, Brian; Kinyanda, Eugene (Tropical Doctor, 2016)
There is a paucity of data on the prevalence of suicidality in HIV/AIDS, and associated psychological factors in sub- Saharan Africa, shown to be high in Uganda. Yet, the region accounts for over 70% of the world HIV burden. Our study used a cross-sectional survey of 226 HIV-positive (HIV+) adults and adolescents (aged 15–17 years) in Mbarara, Uganda. The relationship between suicidality and depressed mood, anxiety symptoms, state anger, self-esteem, trait anger and hopelessness was examined; anger was the predominant factor in suicidality, suggesting that anger management could potentially lower the prevalence of suicidality
Keywords: Suicidality; Suicidal ideation; Suicidal attempt; HIV/AIDS; Psychological correlates; Uganda